Treatment of patients with refractory chronic lymphocytic leukemia with alemtuzumab, alone or in combination with fludarabine - E. V. Kataeva; A. K. Golenkov; E. V. Trifonova; G. A. Dudina; T. A. Mitina; L. L. Vysotskaya; T. D. Lutskaya; I. V. Buravtsova; R. V. Gorenkov; Yu. Yu. Chuksina; V. V. Yazdovskiy (Онкогематология, 2014)
In present study the immediate and long-term therapy results of 14 patients with refractory chronic lymphocytic leukemia (CLL) are analyzed. Treatment program included alemtuzumab alone or in combination with fludarabine.